The Improvement of Mastering Science Concept and Critical Thinking Skill Through Guided Inquiry Learning - Dewi, kustiyanti; Wahyudin, Agus; Putra, Ngurah Made Darma (Educational Management, 2021)
The purpose of this study is to analyze the mastery of science concept and critical thinking skill through guided inquiry learning as an online learning innovation during the Covid 2019 outbreak. The experimental design used was a quasi experimental design in a nonequivalent control group design. The sample of this research was 138 students from 2 Primary Schools in Semarang City. The technique used for collection data was a performance test with multiple choice and questionnaire. The data analysis technique was the classical assumption test including normality test and heteroscedaticity test as well as hypothesis test including different average test, path analysis, effectiveness test, direct effect test and indirect effect test. The results showed that (1) online guided inquiry learning was effective to improve critical thinking skills, (2) online guided inquiry learning was effective to improve the mastery of science concept, (3) there was a positive effect of guided inquiry learning toward critical thinking skill, (4) ) there was a positive effect of guided inquiry learning toward the mastery of science concept, (5) there was a direct effect of critical thinking skill toward the mastery of science concept, (6) critical thinking skill mediated the effect of guided inquiry learning toward the mastery of science concept. In conclusion, guided inquiry learning is effective and has a direct and indirect positive effect toward critical thinking skill and the mastery of science concept.